2021
DOI: 10.3390/ma14143777
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Potentially Toxic Elements in Contaminated Soils Using Thermally Treated Natural Zeolite

Abstract: Rehabilitation of contaminated soils is a complex and time-consuming procedure. One of the most cost-effective and easy-to-use soil remediation approaches is the use of amendments that stabilize the potential toxic elements (PTE) in soil by reducing their mobility and bioavailability. The stabilization of Cu, Pb, Zn, Cd, Co, Cr, Ni in a contaminated soil using 5% and 10% amendment with thermally treated natural zeolite was investigated using a sequential extraction procedure, contamination and environmental ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, Kuldeyev et al [ 98 ] reported high adsorption capacities (94–98 %) for Cd, Ni and Pb from heavily polluted waters, using natural zeolites with a particle size of 3 mm, thermally treated at 500 °C in an inert atmosphere. A higher immobilization effect for heavy metals was reported using 10 % thermally treated natural zeolite at 200 °C for 2 h as soil amendment [ 130 ] compared with air-dried zeolitic material [ 94 ].…”
Section: Methodologies Applied To Natural Zeolites To Improve Their P...mentioning
confidence: 99%
“…However, Kuldeyev et al [ 98 ] reported high adsorption capacities (94–98 %) for Cd, Ni and Pb from heavily polluted waters, using natural zeolites with a particle size of 3 mm, thermally treated at 500 °C in an inert atmosphere. A higher immobilization effect for heavy metals was reported using 10 % thermally treated natural zeolite at 200 °C for 2 h as soil amendment [ 130 ] compared with air-dried zeolitic material [ 94 ].…”
Section: Methodologies Applied To Natural Zeolites To Improve Their P...mentioning
confidence: 99%
“…Samples were digested using a Speedwave XPERT (Berghof, Eningen, Germany) microwave digestion system with HNO 3 65% in the case of water samples and aqua regia (HNO 3 65%:HCl 37% (v/v) = 1:3) in the case of solid (soil and sediment) samples [29]. Fe, Na, Mg, K, and Ca were determined using a 5300 Optima DV (PerkinElmer, MA, USA) Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES), while Ni, Cr, Cu, Zn, Cd, Pb, Mn, Al, and As were determined with an ELAN DRC II Inductively Coupled Mass Spectrometer (PerkinElmer, MA, USA).…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
“…Thus, since 2010, agriculture has already destroyed or radically transformed 70% of grasslands, 50% of savannas, 45% of temperate deciduous forests and 25% of tropical forests [18]. Against these volumes, the increase in production has been only 20% [19]. With the felling of tropical forests, the exploitation of marginal lands and the use of intensive techniques, agriculture has become the planet's main environmental threat, consuming a large percentage of the earth's surface, destroying habitats, depleting water resources, polluting rivers and oceans and being one of the main (24%) sources of anthropogenic greenhouse gas emissions [20].…”
Section: Soil Desertification and Sustainable Use Of Fertilizersmentioning
confidence: 99%